2008
DOI: 10.1111/j.1365-2966.2008.13954.x
|View full text |Cite
|
Sign up to set email alerts
|

Centimetre-wave continuum radiation from the ρ Ophiuchi molecular cloud

Abstract: The ρ Oph molecular cloud is undergoing intermediate‐mass star formation. Ultraviolet radiation from its hottest young stars heats and dissociates exposed layers, but does not ionize hydrogen. Only faint radiation from the Rayleigh‐Jeans tail of ∼10–100 K dust is expected at wavelengths longwards of ∼3 mm. Yet cosmic background imager (CBI) observations reveal that the ρ Oph W photodissociation region is surprisingly bright at centimetre wavelengths. We searched for interpretations consistent with the Wilkinso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
128
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(132 citation statements)
references
References 71 publications
2
128
1
Order By: Relevance
“…Yet CBI observations revealed that the ρ Oph W PDR is surprisingly bright at centimetre wavelengths (Casassus et al 2008). The WMAP 33 GHz image confirms that the general location of the signal seen by CBI is offset by 10 from the centroid of the WMAP 94 GHz data, located on the Oph A core.…”
Section: Introduction and Mapssupporting
confidence: 60%
See 2 more Smart Citations
“…Yet CBI observations revealed that the ρ Oph W PDR is surprisingly bright at centimetre wavelengths (Casassus et al 2008). The WMAP 33 GHz image confirms that the general location of the signal seen by CBI is offset by 10 from the centroid of the WMAP 94 GHz data, located on the Oph A core.…”
Section: Introduction and Mapssupporting
confidence: 60%
“…The situation is even worse for the warm ionised medium (WIM) component (n H < 1 cm −3 ). The spinning dust emission of these regions must therefore include a significant contribution from gas which is denser by at least a factor of 10, as suggested by Casassus et al (2008) and Castellanos et al (2011). In the preliminary models of the Perseus and ρ Ophiuchi regions presented below, we show that, assuming plausible physical conditions and PAH size distributions, spinning dust emission from dense gas can explain most of the AME.…”
Section: Modelling the Anomalous Microwave Emission With Spinning Dustmentioning
confidence: 97%
See 1 more Smart Citation
“…The brightest AME regions in the ring are mostly located adjacent to bright thermal dust features, although the brightest AME region does not have a bright thermal dust counterpart. AME has been seen in PDRs around other H ii regions at higher resolution, e.g., in ρ Ophiuchus (Casassus et al 2008) and Perseus (Tibbs et al 2010). λ Orionis has a particularly high emissivity against 545 GHz and τ 353 , but the emissivity against 100 µm is comparable to the average; this indicates that the AME is connected to the colder dust in this region.…”
Section: Diffuse Ame Regionsmentioning
confidence: 86%
“…ρ Ophiuchus. This molecular cloud is another well-known source of AME (Casassus et al 2008;Planck Collaboration XX 2011). It is included in the PCCS2 catalogue, so we unmask the point sources when considering this region.…”
Section: Diffuse Ame Regionsmentioning
confidence: 99%